EORTC-1203-GITCG - the “INNOVATION”-trial: Effect of chemotherapy alone versus chemotherapy plus trastuzumab, versus chemotherapy plus trastuzumab plus pertuzumab, in the perioperative treatment of HER2 positive, gastric and gastroesophageal junction adenocarcinoma on pathologic response rate: a randomized phase II-intergroup trial of the EORTC-Gastrointestinal Tract Cancer Group, Korean Cancer Study Group and Dutch Upper GI-Cancer group - Wagner, Anna Dorothea; Grabsch, Heike I.; Mauer, Murielle; Marreaud, Sandrine; Caballero, Carmela; Thuss-Patience, Peter; Mueller, Lothar; Elme, Annelie; Moehler, Markus Hermann; Martens, Uwe; Kang, Yoon-Koo; Rha, Sun Young; et al. (BMC Cancer, 2019)
Background 10–20% of patients with gastric cancer (GC) have HER2+ tumors. Addition of trastuzumab (T) to cisplatin/fluoropyrimidine-based chemotherapy (CT) improved survival in metastatic, HER2+ GC. When pertuzumab (P) was added to neoadjuvant T and CT, a significant increase in histopathological complete response rate was observed in HER2+ breast cancer. This study aims to investigate the added benefit of using both HER2 targeting drugs (T alone or the combination of T + P), in combination with perioperative CT for localized HER2+ GC. Methods This is a prospective, randomized, open-label, phase II trial. HER2 status from patients with resectable GC (UICC TNM7 tumor stage Ib-III) will be centrally determined. Two hundred and-fifteen patients from 52 sites in 14 countries will be centrally randomized (1:2:2 ratio) to one of the following treatment arms: Standard: CT alone. CT regimens will be FLOT (5-FU, leucovorin, oxaliplatin, taxotere) CapOx (capecitabine, oxaliplatin) or FOLFOX (5-FU, leucovorin, oxaliplatin) according to investigator’s choice in Europe, and cisplatin/capecitabine in Asia. Experimental arm 1 : CT as in control group, plus T (8 mg/kg loading dose, followed by 6 mg/kg every 3 weeks) at day 1, independent of CT chosen for 3 cycles of 3 weeks before and after surgery. Experimental arm 2: CT plus T as in experimental arm 1, plus P (840 mg every 3 weeks) on day 1. Adjuvant treatment with T or T + P will continue for 17 cycles in total. Stratification factors are: histology (intestinal/non-intestinal); region (Asia vs Europe); location (GEJ vs non-GEJ); HER2 immunohistochemistry score (IHC 3+ vs IHC 2+/FISH+) and chemotherapy regimen. Primary objective is to detect an increase in the major pathological response rate from 25 to 45% either with CT plus T alone, or with CT plus the combination of T and P. Discussion Depending on the results of the INNOVATION trial, the addition of HER2 targeted treatment with either T or T and P to CT may inform future study designs or become a standard in the perioperative management HER2+ GC. Trial registration This article reports a health care intervention on human participants and was registered on July 10, 2014 under ClinicalTrials.gov identifier: NCT02205047 ; EudraCT: 2014–000722-38.